Advances in practical applications of agents, multi-agent systems, and complexity : the PAAMS Collection : 16th International Conference, PAAMS 2018, Toledo, Spain, June 20-22, 2018, Proceedings /: the PAAMS Collection : 16th International Conference, PAAMS 2018, Toledo, Spain, June 20-22, 2018, Proceedings. (2018) - Unknown
No abstract available